A 0.5-V Four-Stage Amplifier Using Cross-Feedforward Positive Feedback Frequency Compensation - Feifan Gao; Pak Kwong Chan (Chips, 2023)
This paper presents a low-voltage CMOS four-stage amplifier operating in the subthreshold region. The first design technique includes the cross-feedforward positive feedback frequency compensation (CFPFC) for obtaining better bandwidth efficiency in a low-voltage multi-stage amplifier. The second design technique incorporates both the bulk-drain-driven input stage topology in conjunction with a low-voltage attenuator to permit operation at a low voltage, and improves the input common-mode range (ICMR). The proposed circuit is implemented using TSMC-40 nm process technology. It consumes 0.866 μW at a supply voltage of 0.5 V. With a capacitive load of 50 pF, this four-stage amplifier can achieve 84.59 dB in gain, 161.00 kHz in unity-gain bandwidth, 96 deg in phase margin, and 5.7 dB in gain margin whilst offering an input-referred noise of 213.63 <semantics>nV/<msqrt>Hz</msqrt></semantics> @1 kHz, small-signal power-bandwidth FoMss of 9.31 (MHz∙pF/μW), and noise-power per bandwidth-based FoMnpb of 1.15 × 10−6 ((<semantics>µV/<msqrt>Hz</msqrt></semantics>)·µW/Hz). Compared to the conventional bulk-driven input stage design technique, it offers improved multi-parameter performance metrics in terms of noise, power, and bandwidth at a compromising tradeoff on ICMR with respect to bulk-driven amplifier design. Compared with conventional gate-source input stage design, it offers improved ICMR. The amplifier is useful for low-voltage analog signal-processing applications.